Peranan Badan Permusyawaratan Desa (BPD) Dalam Mewujudkan Otonomi Desa di Desa Sereang - FITRIYANI FITRIYANI (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research aimed to determine the role of Village Consultative Bureau (BPD) in realizing Sereang Village autonomy system and all affecting factors. This research was a descriptive research using case study approach. The research was conducted at Sereang Village of Maritengngae District in Sidenreng Rappang Regency. The population were 701 heads of family and seventy (70) of them accounted as sample. Research data was collected through observation, interviews, questionnaires with BPD members and Sereang people. The results showed that the role of Village Consultative Bureau (BPD) in realizing Sereang Village autonomy system was not yet run optimally viewed from the legislative function by scoring 75,71% unfavorable, very good representation at 80%, and control functions were poor at 61,42%. The factors affecting the role of Village Consultative Bureau (BPD) in realizing Sereang Village autonomy system were poor education at 47,14%, experience at 50%, and severely hampered infrastructure at 61,42%.